The Potential of Materials Constructing Traditional Houses of Honai Dani Tribe of Papua as A Source for Learning Biochemistry with an Ethnoscience Approach - Rahmadana, Arini; Siti Sriyati; liliawati, Winny (Journal of Tropical Chemistry Research and Education, 2025)
This research aims to explore the biochemical aspects of the local wisdom of the Honai traditional house Dani tribe of Papua and its potential integration in biochemistry learning through an ethnoscience approach. The research method is literature study from scientific journal articles, books, online articles, and research reports related to the biochemical composition of the building materials that make up the Honai traditional house.  The main problem in this study is how to construct indigenous science knowledge into scientific science and identify its potential integration in biochemistry learning. The study showed that the main components of Honai houses are reeds, various types of wood, and rattan. The biochemical composition is lignin, holocellulose, alpha-cellulose and hemicellulose as well as other compositions that can be discussed on the topic of biochemical aspects of living things and further on the topic of cells and cell bonds / chemical bonds. The material composition contained in the materials that make up the honai traditional house can also be further explored in the practice of applied biochemistry, to produce other appropriate items. Thus the Honai traditional house is highly potential as a learning resource in biochemistry courses with an ethnoscience approach.